Growth, water use, yield and quality parameters in oregano affected by reduced irrigation regimes. (20th August 2020) - Hancioglu, Nurten E; Kurunc, Ahmet; Tontul, Ismail; Topuz, Ayhan
Abstract: BACKGROUND: Determining plant tolerance to water stress is necessary in irrigation scheduling, decisions concerning supplementary irrigation, planning and operation and, more importantly, the rational use of water resources. In the present study, effects of the irrigation regime on oregano growth, water use, yield and quality parameters were investigated using reduced irrigation regime treatments. RESULTS: Increased water stresses caused a decrease in all growth and yield parameters. Plant water use efficiency was not significantly different among the control, low and medium stress treatments, although it was the lowest for the extreme water stress treatment. Total essential oil yield was the only quality parameter demonstrating significant differences among treatments. Yield response factors were determined as 1.13, 1.12, 1.06 and 1.10 for total fresh, total dry, dry leaf and total essential oil yields, respectively. CONCLUSION: Yield response factors indicate that oregano plant is slightly sensitive to water stress. Although the yield parameters were affected by water stress, Origanum onites, under cultivation in recent years, might have developed a resistance mechanism for quality parameters because it has grown in very dry conditions under a natural environment for many years. However, the negative relationships between crop evapotranspiration versus essential oil, total phenolic and flavonoid contents and extract yield indicates that the quality parameters of oregano under low plant water consumption may be increased. © 2020 Society of Chemical Industry